IMPLEMENTASI NILAI-NILAI KEARIFAN LOKAL ETNIS ALOR DALAM MENGUATKAN TOLERANSI MELALUI MATA PELAJARAN PKN DI KELAS IV SD - Tut, Rusmin Mulyadin; Suswandari; Ihsana El Khuluqo (Jurnal Edukasi, 2025)
The aim of this research is to describe the implementation of the local wisdom values of the Alor ethnic group which contains the meaning of tolerance, divided into three dimensions, namely the local wisdom of the Alor ethnic group which is related to religiosity, nature and fellow humans. Religion, as a religious community, implements cultural values between people in traditional baloe (new eating) rituals and preserves the nature that has been passed down from ancestors. The method used is qualitative research with a case study approach. Informants in the research included school principals, teachers, students, traditional leaders, community leaders and religious leaders. Participant observation, in-depth interviews and documentation were used as tools to collect research data. Data validity with source triangulation. The findings in this research are that students get used to respecting and respecting each other in terms of differences in ethnicity, religion and race, then getting students used to being involved in implementing cultural values that have been passed down from their ancestors and carrying out their obligations as religious people.